Respostas antioxidativas, fisiológicas e produtiva de arroz cultivado sob deficiência hídrica e adubação silicatada - Moro, Adriana Lima; Broetto, Fernando [UNESP]; Moro, Edemar (Universidade Estadual de Londrina, 2015)
Silicon is a nutrient that can provide better development of rice plants grown in environments with water deficit. This element reduces water loss by transpiration, increases photosynthetic rate and acts as an activator of the enzyme defense system. The purpose of this research was analyse the effect of silicon in two rice cultivars (Curinga and IAC 202) submitted to water deficit under the enzymatic parameters, physiological and productive. We used four strains of soil water (-10, -30, -50 and -70 kPa) combined with two ways of correcting the soil saturation (absence and presence of silicon). We measured the enzymatic activity of Superoxide dismutase, catalase and ascorbate peroxidase, the rate of CO2 assimilation and yield. The experimental design was randomized in blocks 4 x 2 factorial with four replications, and the means compared by Tukey test (p <0.05). The enzyme activity increased with the application of silicon even in intense water deficit. The CO2 assimilation rate and also grain yield increased with the addition of silicon. The application of silicone on both cultivars alleviate the effects of stress caused by lack of water.
Antioxidative responses, physiological and productive of rice grown under water deficit and silicon fertilization
Keywords: CO2 assimilation; SOD; Stress